'Advertisements or adverse-tisements?'—An accessibility barrier for persons with visual impairments. (12th October 2018) - Nengroo, Ab Shaqoor; Kuppusamy, K S
Abstract: Web accessibility refers to allowing people with diverse capabilities to use the Internet, interact with it and contribute to it. The Web offers content and services to users, which is primarily monetized through advertisements. Web accessibility issues arise when a homogeneous team of web designers and developers produce homogeneous content and services for a very heterogeneous group of Internet users and ignores the web accessibility guidelines. One such content is Internet advertisements whose volume on web pages has increased significantly from last decade. In this paper, we shed light on how advertisements can cause various accessibility barriers to persons with visual impairments. This study also attempts to identify the potential determinants and various advertisement formats, which cause multiple accessibility barriers. Our findings indicate that advertisements lack accessibility features, which cause the disturbance (63%), insecure feelings (63%), user performance decrease (60%), content obstruction (90%), Web page backtrack issues (90%) and security issues (20%) for persons with visual impairments. To decrease the intensity of advertisement-related barriers, we have proposed some solutions and advertisement creation techniques and tweaks, which can be followed by designers and developers to improve the accessibility of these web advertisements.